Accounting history: a bibliometric literature review - Cepêda, Catarina; Monteiro, Albertina Paula; Silva, Rui; Ferreira-da-Silva, Amélia (RC&C: Revista de Contabilidade e Controladoria, 2022)
Accounting is much more than a science, is a branch of our heritage history. Since the dawn of primitive era, it has been a part of us and kept developing. Given its importance, the literature in accounting history has grown but much remains to be unravelled. In this sense, this research is a literature review on the evolution of accounting. The aim is to highlight the accounting timelessness in humanity and to analyse the scientific production in accounting history. A quantitative bibliometric analysis was conducted using VOSviewer and R Bibliometrix software. A total of 236 publications were selected from the Web of Science database, between 1975 and 2021. In this research, we found that the main subtopics in accounting history research are: (1) accounting history and its relevance, (2) the roles of accounting in society, (3) accounting and religion and (3) schools of thought in accounting history. Australia, England, America, and Italy are the countries with most published articles. “Accounting History”, “Accounting Organizations and Society” and “Accounting Historians Journal” have been among the top journals, Garry Carnegie, Delfina Gomes and Christopher Napier are the most influential authors and the institutions, like Rmit University, the University of Minho and Cardiff University, stand out on accounting history research, considering the number of publications. The research trend and the progress in accounting history were discussed.